The implementation of strategic partnering in industrialised building system / Faridah Muhamad Halil - Muhamad Halil, Faridah (2013)
The concept of strategic partnering is an important consideration for the players in the construction industry. The research has revealed that strategic partnering is about long term relationship practiced between two or more parties in projects awarded by the clients. Strategic partnering in construction has been presented as a potentially important way of improving construction project performance through the direct benefits received by the clients such as quality, project success, less delay, less problem, social benefits and sustainable business. The aim of the research is to develop a conceptual framework for the implementation of strategic partnering in the industrialised building system. The methodology adopted in this research is mixed method consisting of literature search, questionnaire survey and semi-structured interview's. The benefits of using this method are that it presents an opportunity to seek verification in the results from different methods, and also to seek similar or different pattern as well. Using this approach, the targeted of respondents are selected are public and private clients. The findings of this research are derived from the literature review, questionnaire survey and semi structured interviews. Both public and private clients understand the concept of strategic partnering in terms of definition, contractual procedure, procurement method and suitability of the project. It can be ascertained from the results; public clients described strategic partnering as a commitment and shared goals between stakeholders whilst private clients described it as a trust relationship between stakeholders. The majority of public and private clients in Malaysia are found to use PAM and PWD the standard form of contract during the strategic partnering exercise in IBS projects. In terms of procurement method, public clients mostly use design and build while private clients uses the traditional method in strategic partnering practice in the IBS projects. Both public and private clients indicated that mass construction, complexity of the projects and long term development o f IBS projects are suitable to practice strategic partnering. However, for partnering charter, private clients were unfamiliar with this approach in the contractual practice in strategic partnering. Win-win situation received by public and private clients through practicing this approach, public clients revealed that they received social benefits and cost saving as compared to private clients where they gained in terms of return on investment and profit. One of the outcome of this research is a conceptual framework developed which is suitable as a reference for the Malaysian construction industry players practicing strategic partnering in IBS construction approach. Its guide the industry player’s towards a better understanding and successful implementation of strategic partnering as planned in the Construction Industry Master Plan Malaysia 2006-2015 (C1MP).